Caracterização citogenética de espécies da família Heptapteridae (Teleostei, Siluriformes) das bacias dos rios Cuiabá (MT) e Ivaí (PR) - Barbosa, Ligia Magrinelli (2012)
The Heptapteridae family is endemic to the Neotropics, but their phylogenetic relationships are still not well established, and cytogenetic studies are still scarce. In this work, cytogenetic studies were made on specimens of Pimelodella sp and Pimelodella taenioptera from Cuiabá river basin, MT and Imparfinis schubarti from Ivaí river basin, PR. The diploid number of Pimelodella sp individuals was 46 chromosomes, with a karyotype composed of 26m+10sm+10st and NF=92. This specie presented a secondary constriction in the 14th pair (submetacentric) coinciding with the nucleolar organization region. A heteromorphism in NOR size between homologous chromosomes was also observed. FISH using 18S rDNA probes showed marks equivalent to those obtained by silver nitrate. The constitutive heterochromatin pattern of this specie showed weak telomeric and centromeric markings. However, this specie presented a well-defined interstitial heterochromatin block on the short arms of the 14th pair (submetacentric). The cytogenetic analysis of Pimelodella taenioptera showed a diploid number of 2n = 52 chromosomes with a karyotype composed of 26m+22sm+4st and NF=104. Pimelodella taenioptera had a simple NOR system in the terminal position of the short arm of a submetacentric pair number 14, as evidenced by FISH using 18S rDNA probes. This species presents a heterochromatin pattern with telomeric, pericentromeric and interstitial labeling; however the interstitial labeling were more frequently. All Imparfinis schubarti specimens analyzed had a 2n=58 chromosome number and a karyotype of 28m+28sm+2st, with a fundamental number of 116. A conspicuous secondary constriction was seen in the long arm of the first metacentric chromosome pair. The Ag-NORs were observed in the same region. C-banding of I. schubarti was less evident, showing a well-defined pericentromeric mark in the first metacentric pair, that is the NOR-bearing. In situ hybridization with 18S rDNA probe confirmed the NOR location in the secondary constriction of the first metacentric chromosome. There are few cytogenetic studies in species of the Heptapteridae family, especially when it xii comes to the Midwest region of Brazil. This work brings a contribution to the cytogenetic knowledge of species of the Heptapteridae family in the Midwest region of Brazil.